CFD Applied to the Analysis of the Operation of a Solar Still Pyramidal-type. Issue 1 (1st September 2022) - Terres, H; Chávez, S; Lizardi, A; Lara, A; Morales, J; Rodríguez, R; Ruiz, C
Abstract: This work shows the results obtained for the temperature distributions of the component elements of a pyramidal type solar still. The results of the air velocity and density distributions inside the still are also shown. The results indicate which are and where the maximum values of temperature, density, and airspeed are located. These results are useful because they help to establish how the geometry of the still influences its operating process. The study by the CFD technique turns out to be very useful because it allows the formulation of design criteria regarding the geometry of the still and how they could make improvements in the use of solar energy in solar stills.